In Defiance of Boundaries : Anarchism in Latin American History - Shaffer, Kirwin R.; Laforcade, Geoffroy de (Book collections on Project MUSE., 2015)
This edited collection is the first to sample the new wave of scholarship on Latin American anarchism to trace the transnational anarchist presence in Latin America at the turn of the twentieth century. The essays examine urban and rural movements, indigenous resistance, race, gender, sexuality, and social and educational experimentation.